Supporters Marching - Manuel Echavarria::::::photographer:::
During the early 1970's, UFW organizers and supporters took to the streets more than once to dramatize the union struggle. Durante los primeros años de la década del 70, organizadores y partidarios de la UFW se lanzaron a las calles más de una vez para enfatizar la dramática lucha de la UFW.